Kirjallisuuden kääntäminen on teknologisoitumisen kynnyksellä – mutta mitä kääntäjät oikeasti tarvitsevat? Raportti työpajasta ”Kaunokirjallisuuden kääntäminen ja (käännös)teknologia: tutkimuksen, käytännön ja juridiikan näkökulmia”, XXII KäTu-symposiumi, Helsingin yliopisto, 12.4. 2025 - Taivalkoski-Shilov, Kristiina (Finland, 2026)
This article reports on the workshop “Literary Translation and (Translation) Technology considered from Research, Practice and Legal Perspectives”, which took place at the XXII KäTu Symposium on Translation and Interpreting Studies on EF April FHFI at the University of Helsinki. It was organized by the project Narrative Text, Translator and Machine (University of Turku, FHFF–FHFR), funded by the Research Council of Finland. The aim was to share knowledge on recent research on technology-assisted literary translation and to engage in a dialogue with professionals. The workshop opened with three papers, by Claudine Borg (University of Malta), Lauri Niskanen (University of Turku), and Maarit Koponen (University of Eastern Finland). The second part consisted of a panel discussion. The speakers were translators Jaakko Kankaanpää and Riina Vuokko from the Literary Translators’ Branch of the Union of Journalists in Finland, translator Nina Mäki-Kihniä, who is an advisory board member of the Narrative Text project, and Niina Vettensola, LL.M., who is the Executive Director of Sanasto, the Finnish literary copyright society.